2019
DOI: 10.9734/jeai/2019/v40i330364
|View full text |Cite
|
Sign up to set email alerts
|

Control of Alternaria alternata Using Melaleuca Essential Oil (Melaleuca alternifolia)

Abstract: Aims: This study aimed to evaluate the fungitoxic potential of melaleuca essential oil on the mycelial growth of Alternaria alternata under in vitro condition and the treatment of cowpea beans. Study Design: The experiments comprised completely randomized designs: Eleven treatments with five replicates on in vitro test; and six treatments with five replicates on in vivo test. Place and Duration of Study: The work was carried out at the Center for Agrifood Science and Technology of the Federal Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…ex Briq) and tea tree ( Melaleuca alternifolia (Maiden & Betche) Cheel) essential oils were from Flora Srl (Lorenzana, Pisa, Italy). The selection of these essential oils was based initially on their availability in our laboratory, and then on the studies in the literature that have reported in vitro activities of some of these against pathogen growth [ 65 , 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…ex Briq) and tea tree ( Melaleuca alternifolia (Maiden & Betche) Cheel) essential oils were from Flora Srl (Lorenzana, Pisa, Italy). The selection of these essential oils was based initially on their availability in our laboratory, and then on the studies in the literature that have reported in vitro activities of some of these against pathogen growth [ 65 , 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…(KOUASSI et al, 2017), cinnamon (C. verum) (YEOLE et al, 2014) and clove (S. aromaticum) (ABBASZADEH et al, 2014). Alves et al (2019) evaluated the in vitro control of Alternaria alternata (Fr.:Fr.) Keissl.…”
Section: Discussionmentioning
confidence: 99%
“…(75.21%). Alves et al (2019) detected that tea (M. alternifolia) essential oil had a strong antifungal activity 224 (MIC = 14.49 µg/ml) against A. alternata. Hamdani and Allem (2015) determined the antifungal activity of the leaf essential oil from citrus (C. limon, C. sinensis, and C. reticulata) and found that the concentration of 1000 μg/ml was sufficient to inhibit the development of A. alternata.…”
Section: In Vitro Antifungal Activitymentioning
confidence: 99%